A Critical Analysis of Right to Life and Judicial Intervention in South Asian Countries - Prakash, K. C. (Kathmandu School of Law Review, 2013)
Right to life is a phrase that describes the belief that a human being has an essential right to live, particularly that a human being has the right not to be killed by another human being. The concept of right to life is central to debates on the issues of capital pun ishment, self defense, abortion and war. Pro-life is a term representing a variety of perspectives and activist movements in medical ethics. It is most commonly used, especially in the media and popular discourse, to refer to opposition to abortion. More generally, the term describes a political and ethical view which maintains that human fetuses and embryos are persons and therefore have a right to live. Less commonly, it can be used to indicate abortion. Right to life is based on three things as food, clo th and shelter.